Running with wolves - Dutcher, Jim, 1943-; Dutcher, Jamie; National Geographic Kids (Firm); National Geographic Society (U.S.) (Washington, DC : National Geographic Kids, 2019)
Discover the wonder of wolves from Emmy-award winning filmmakers Jim and Jamie Dutcher as they tell their story of the six years they watched, learned about, and lived with the Sawtooth wolf pack. Adventure, friendship, and family come together in this riveting memoir as two award-winning filmmakers take you through the experience of the years they spent living in the wild with a real-life wolf pack. Jim and Jamie set out to show the world that instead of fearsome beasts, wolves are social, complex, and incredible creatures that deserve our protection. Deep in the mountain wilderness of Idaho, they set up Wolf Camp, where they spent years capturing the emotional, exciting, and sometimes heartbreaking story of their pack. Meet Kamots, the fearless leader. Learn from wise Matsi. Explore the forest with shy Lakota. And watch as adorable pups grow from silly siblings to a devoted pack. See how these brave wolves overcome all odds, battling mountain lions and frigid temperatures. Most of all, discover the surprising kindness, compassion, and devotion that Jim and Jamie discovered by living with wolves.
A wolf's trust -- Longing for wilderness -- A bright idea -- Begininnings of the Sawtooth pack -- Trouble in the pack -- Season of change -- A compassionate alpha -- A gut-wrenching decision -- New adventures -- Two leaps forward -- Friends for Lakota -- Call of the wolf -- Family ties -- Celebration! -- Time to say goodbye.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Age 10+
Grade 7 to 8.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Wolves -- Anecdotes -- Juvenile literature; Wolves -- Behavior -- Juvenile literature; Wolves -- Idaho -- Sawtooth Wilderness; Social behavior in animals -- Idaho -- Sawtooth Wilderness; Wolves; Wolves -- Behavior; Electronic books- OSLIS; Electronic books; New titles added; Anecdotes; Juvenile works